PREVALENCE OF GASTROINTESTINAL PARASITES IN KOREAN NATIVE GOATS (C APRA HIRCUS AEGAGRUS) - E. B. Gebeyehu; M. G. Seo; B. Y. Jung; J. W. Byun; J. K. Oem; H. Y. Kim; D. Kwak (Journal of Animal and Plant Sciences, 2013)
The current study was conducted to investigate the prevalence and intensity of gastrointestinal (GI) parasites in Korean native goats (Capra hircus aegagrus). Fecal samples from 241 goats in 57 herds were collected and examined for parasite eggs/oocysts and counted by using standard qualitative and quantitative techniques. A total of 167 (69.3%) goats were found to be infected with one or more GI parasites. Of these, 163 (67.6%) were infected by coccidia, 54 (22.4%) by nematodes and 5 (2.1%) by cestodes. Eimeria spp. was the only coccidian parasite identified while strongyle group (20.7%) was the most prevalent nematode detected. The prevalence of Eimeria was significantly higher (P<0.05) than that of the other GI parasites. Heaviest parasitic load was observed for Strongyloides (23.5%) although its prevalence was lower compared to other GI parasites. In addition, mixed parasitic infections were found in 31.7% of the goats. Higher odds of goats being infected by all GI parasites were observed for adults than in young goats except for Moniezia. Since parasitic infections result in decreasing productivity leading to economic loss, a well-coordinated and permanent sanitary monitoring is suggested.
Keywords: Gastrointestinal parasites; Korean native goats; Capra hircus aegagrus; Prevalence